Goin' someplace special - McKissack, Pat, 1944-2017.; Pinkney, Jerry (New York : Atheneum Books for Young Readers, 2001)
In segregated 1950s Nashville, a young African American girl braves a series of indignities and obstacles to get to one of the few integrated places in town: the public library.
"An Anne Schwartz book."
Keywords: Segregation -- Fiction; African Americans -- Fiction; Nashville (Tenn.) -- Fiction